The academic libraries & the social responsibility challenge: REBIUN report. - (:unkn) unknown (REBIUN, 2014)
Póster presentado en World Library and Information congress - 80th IFLA General Council and Congress, Lyon 2014.
Versión impresa disponible con signatura: UPM-BCS- Depósito 1 – Rebiun
Keywords: Bibliotecas universitarias; Gestión de bibliotecas; Responsabilidad social; Sostenibilidad